2001
DOI: 10.1016/s0959-8049(00)00368-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy alone or combined surgery and radiation therapy in squamous-cell carcinoma of the penis?

Abstract: To assess the prognostic factors and the outcome in patients with squamous-cell carcinoma of the penis, a retrospective review of 41 consecutive patients with non-metastatic invasive carcinoma of the penis, treated between 1962 and 1994, was performed. The median age was 59 years (range: 35±76 years). According to the International Union Against Cancer (UICC) 1997 classi®cation, there were 12 (29%) T1, 24 (59%) T2, 4 (10%) T3 and 1 TX (2%) tumours. The N-classi®cation was distributed as follows: 29 (71%) patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 33 publications
2
41
0
2
Order By: Relevance
“…Data on the use of radiotherapy following local resection or microscopically incomplete surgery are very limited. Zouhair et al reported local failures in 25% of patients treated with postoperative radiotherapy for positive surgical margins [40]. These findings compare well with the results of the present study.…”
Section: Regional Relapse N (%)supporting
confidence: 92%
See 1 more Smart Citation
“…Data on the use of radiotherapy following local resection or microscopically incomplete surgery are very limited. Zouhair et al reported local failures in 25% of patients treated with postoperative radiotherapy for positive surgical margins [40]. These findings compare well with the results of the present study.…”
Section: Regional Relapse N (%)supporting
confidence: 92%
“…Penile-sparing local tumor excision produces less emotional impact, but local recurrence rates have been reported to be as high as 32-50% [16]. Lower local recurrence rates can be achieved by the addition of radiotherapy [40].…”
Section: Introductionmentioning
confidence: 99%
“…All these techniques may effectively treat selected patients with distal penile T1 lesions with control rates ranging in several series from 78 to 90% [58][59][60][61][62][63][64][65][66][67][68]. Several investigations have demonstrated that local relapses (10-20%) after radiotherapy can be salvaged with surgery without apparently affecting the prognosis [69]. Approximately 20% of patients with low-stage lesions require subsequent amputation after radiation therapy as a result of recurrent disease or iatrogenic complications [63,68].…”
Section: Treatment Of the Primary Tumourmentioning
confidence: 99%
“…Brachytherapy may be realized using the contact technique used by English authors, or iridium-192 needles interstitial implant. Local recurrence rate after external beam radiotherapy ranges from 15% up to 61% of cases with an organ functional preservation of 39-85% (table 3) [23,24,[38][39][40][41][42]. Better results have been reported after iridium brachytherapy: local recurrence percentage was 5-22% of cases and it was possible to obtain a penile preservation in 39-85% of cases (table 4) [25,[43][44][45][46][47].…”
Section: Reviewmentioning
confidence: 99%